Evaluation of the cell-free DNA integrity index as a liquid biopsy marker to differentiate hepatocellular carcinoma from chronic liver disease - Kumar, Sonu; Nadda, Neeti; Paul, Shashi; Gamanagatti, Shivanand; Dash, Nihar Ranjan; Vanamail, Perumal; Saraya, Anoop; Shalimar,; Nayak, Baibaswata (Frontiers in Molecular Biosciences, 2022)
Background: Hepatocellular carcinoma (HCC) occurs in the majority of patients with underlying chronic liver disease (CLD) of viral and non-viral etiologies, which requires screening for early HCC diagnosis. Liquid biopsy holds great promise now for early detection, prognosis, and assessment of response to cancer therapy. Cell-free DNA (cfDNA) as a liquid biopsy marker can be easily detected by a real-time quantitative PCR (RT-qPCR) assay for a change in its concentration, integrity, and fragmentation in cancer. Methods: Patients with HCC (n = 100), CLD (n = 100), and healthy (n = 30) controls were included in the study. The cfDNA was isolated from serum and real-time quantitative PCR (RT-qPCR) was carried out using primer pairs for large(>205 bp) and small (110 bp) fragments of repetitive elements (ALU and LINE1) and housekeeping genes (ꞵ-Actin and GAPDH). Total cfDNA concentrations and integrity index were determined by the absolute quantitation method (L/S ratio or cfDII-integrity). The cfDII as a measure of fragmentation was determined by comparative Ct (2–ΔΔCt) method of relative quantification (cfDII-fragmentation).Using a receiver operating characteristic (ROC) curve, cfDII-integrity and cfDII-fragmentation were used to differentiate HCC from CLD patients or healthy controls. Results: The total cfDNA concentrations in the sera of HCC (244 ng/ml) patients were significantly higher than those of CLD (33 ng/ml) patients and healthy (16.88 ng/ml) controls. HCC patients have shown poor DNA integrity or excess cfDNA fragmentation than CLD patients and healthy controls. The cfDII-integrity of GAPDH and ALU significantly differentiate HCC from CLD at AUROC 0.72 and 0.67, respectively. The cfDII-fragmentation following normalization with cfDNA of healthy control has shown significant differential capabilities of HCC from CLD at AUROC 0.67 using GAPDH and 0.68 using the ALU element. The ROC curve of LINE1 and ꞵ-actin cfDII was not found significant for any of the above methods.The cfDII-fragmentation trend in HCC patients of different etiologies was similar indicating increased cfDNA fragmentation irrespective of its etiology. Conclusions: The cfDII measuring both DNA integrity (L/S ratio) and fragmentation of the Alu and GAPDH genes can differentiate HCC from CLD patients and healthy individuals.